Riboflavin acetate induces apoptosis in squamous carcinoma cells after photodynamic therapy - Juarez, Andrea Virginia (2015)
Several research efforts have been focused on finding newer and more efficient photosensitizers for photodynamic therapy (PDT). Although, it was demonstrated that riboflavin is an efficient photosensitizer for PDT, the effect of its ester derivate, riboflavin 2′,3′,4′,5′-tetraacetate (RFTA), which has higher cellular uptake, has not been well defined. To evaluate the cell death generated by applying RFTA as the photosensitizer in PDT in a human cancer cell line of squamous carcinoma (SCC-13), these cells were incubated with riboflavin and its ester derivate, RFTA followed by irradiation with different blue light doses. Cell viability was evaluated using neutral red uptake assay and cell death was evaluated using transmission electron microscopy, TUNEL assay and annexin V-PE/7AAD double staining. The expression of caspase-3, Bax, Bcl-2, ERK 1/2 and p38MAPK was evaluated by Western blotting and generation of intracellular ROS and changes in anion superoxide levels were analyzed using 2′,7′-dichlorofluorescein-diacetate and dihydroethidium dye, respectively. RFTA-PDT generated a decrease in cancer cell viability in a light dose–response. Treated SCC-13 cells exhibited chromatin condensation, formation of apoptotic bodies, increases in TUNEL-positive cells, phosphatidylserine externalization and decreased procaspase-3 and Bcl-2 protein expression and increment of ERK 1/2 phosphorylation. Moreover, trolox abolished the effect of PDT on cell viability linking the increase in intracellular ROS levels with the cell death observed, whereas that the pre-treatment with MEK inhibitor did not induce changes in SCC-13 cell survival. These findings demonstrate the effects of RFTA in triggering apoptosis induced by ROS (Ø2−) production after visible light irradiation of squamous carcinoma cells.